Real-time tomographic holography for augmented reality - Galeotti, John M. (2010)
The concept and instantiation of Real-Time Tomographic Holography (RTTH) for augmented reality is presented. RTTH enables natural hand-eye coordination to guide invasive medical procedures without requiring tracking or a head-mounted device. It places a real-time virtual image of an object's cross-section into its actual location, without noticeable viewpoint dependence (e.g. parallax error). The virtual image is viewed through a flat narrow-band Holographic Optical Element with optical power that generates an in-situ virtual image (within 1 m of the HOE) from a small SLM display without obscuring a direct view of the physical world. Rigidly fixed upon a medical ultrasound probe, an RTTH device could show the scan in its actual location inside the patient, even as the probe was moved relative to the patient.